Synthesis and modelling of functionalized UiO-66 metal organic frameworks for gas adsorption - Mohammad Latif, Muhammad Alif; Tuan Kob @ Yaakub, Tuan Nurul Azura; Abdul Rahman, Mohd Basyaruddin; Gandara, Felipe (Persatuan Sains Analisis Malaysia (ANALIS), 2024)
In this article, we present our experimental and computational findings on the adsorption of ethylene gas within variations of UiO66 metal-organic frameworks (MOFs). UiO-66 MOF was functionalized with 2-vinylbenzoic acid (2VBA), 3-vinylbenzoic acid (3VBA), and 4-vinylbenzoic acid (4VBA) and characterized using powder X-ray diffraction techniques, FT-IR analysis and 1H NMR. Based on structural analysis, the functionalized UiO-66 MOFs were found to possess the same structural stability as the 3D porous crystalline lattices of UiO-66, with hexanuclear zirconium oxyhydroxide clusters (Zr6O4(OH)4(RCO2)12. Grand Canonical Monte Carlo simulation showed that the average loading of ethylene gas in UiO-66 and functionalized UiO-66 were relatively close. The adsorption was further investigated using radial distribution function analysis and it was found that the most favorable interactions were between the adsorbate and the carbon atom of the MOFs. These interactions were crucial for ethylene stabilization inside UiO-66 pore channels. The results presented here supported the viability of ethylene adsorption in UiO-66's modified terephthalate linker by demonstrating that functionalized UiO-66 not only retain structural integrity, but also have comparable ethylene adsorption at different pressures with stronger interactions with ethylene gas.